ĐO THAM SỐ CHẤN ĐỘNG RUNG TRONG QUẢN LÝ MÔI TRƯỜNG BẰNG CÁC MÁY THĂM DÒ ĐỊA CHẤN - Tấn, Vũ Trọng; Thu, Nguyễn Ngọc; Quyên, Võ Thị Hồng (Vietnam Journal of Earth Sciences, 2011)
Vibration testing method in environmental management using seismic recording systemNowaday, industrial activities often face to environmental impacts exceeding safety levels. To control these effects, local authorities should examine characteristic factors of undertaking actions regularly; apply modern monitoring methods to get more accuracy and convenience. The article introduces a method of monitoring blast vibration parameters in Dong Nai province using seismic recording systems.